2015
DOI: 10.11646/zootaxa.3931.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Coreoleuciscus aeruginos (Teleostei: Cypriniformes: Cyprinidae), a new species from the Seomjin and Nakdong rivers, Korea

Abstract: Coreoleuciscus splendidus was first reported as a monotypic species. Recent morphological and genetic studies have revealed that the species is represented by two disjunct and distinct lineages. The two lineages of C. splendidus include populations inhabiting the Han and Geum rivers in the East Korea Subdistrict and populations inhabiting the Seomjin and Nakdong rivers in the South Korea Subdistrict. In this study, significant differences were found between these two independent lineages through a high degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The following supporting information can be downloaded at: , Figure S1: Time tree of Huigobio and its close relatives based on 13 protein-coding genes of mitochondrial genomes; Table S1: Reviews of the genetic diversity of freshwater fishes endemic to southern China revealed by mitochondrial genes; Table S2: Reviews of the phylogeographical patterns of freshwater fishes endemic to southern China revealed by mitochondrial genes; Table S3: Primers and annealing temperature used in PCR amplification of mitochondrial genomes; Table S4: Sampling localities and source of mitochondrial genome for Huigobio and outgroup taxa; Table S5: Comparisons among six models of biogeography analyses in ancestral area reconstruction of H. chenhsienensis . References [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 26 , 27 , 37 , 65 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Figure S1: Time tree of Huigobio and its close relatives based on 13 protein-coding genes of mitochondrial genomes; Table S1: Reviews of the genetic diversity of freshwater fishes endemic to southern China revealed by mitochondrial genes; Table S2: Reviews of the phylogeographical patterns of freshwater fishes endemic to southern China revealed by mitochondrial genes; Table S3: Primers and annealing temperature used in PCR amplification of mitochondrial genomes; Table S4: Sampling localities and source of mitochondrial genome for Huigobio and outgroup taxa; Table S5: Comparisons among six models of biogeography analyses in ancestral area reconstruction of H. chenhsienensis . References [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 26 , 27 , 37 , 65 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…The two G. naktongensis populations from the two major river systems, the Geum and Nakdong rivers in the West Korea and South Korea subdistricts, respectively, also showed the same biogeographical distribution pattern as those of Coreoleuciscus and Koreocobitis (Kim and Bang 2012 ; Kim et al 2012 ). Each of the two species in both genera was erected as a novel species based on further taxonomic studies, as well as significant genetic divergence (Kim et al 2000 ; Song and Bang 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Coreoleuciscus aeruginos (family Cyrinidae) is an endemic Korean freshwater fish distributed in riffles of the middle and upper reaches of the Seomjingang and Nakdonggang River systems. A single C. aeruginos specimen was previously reported as C. splendidus (Mori 1935), but was later described as a new species with significant morphological and genetic differences from Coreoleuciscus splendidus (Song and Bang 2015). This study first reports the complete mitogenome of the C. aeruginos holotype and provides the phylogenetic location of genus Coreoleuciscus.…”
mentioning
confidence: 82%